A versatile liquid‐jet setup for the European XFEL. (22nd February 2019) - Schulz, J.; Bielecki, J.; Doak, R. B.; Dörner, K.; Graceffa, R.; Shoeman, R. L.; Sikorski, M.; Thute, P.; Westphal, D.; Mancuso, A. P.
Abstract : A versatile liquid‐jet injection system for serial femtosecond crystallography at the SPB/SFX instrument of the European XFEL is presented. The system comprises a load‐lock nozzle rod changer, chamber‐in‐chamber differential pumping, liquid handling systems and two microscopes for sample imaging and diagnostics. Abstract : The SPB/SFX instrument of the European XFEL provides unique possibilities for high‐throughput serial femtosecond crystallography. This publication presents the liquid‐jet sample delivery setup of this instrument. The setup is compatible with state‐of‐the‐art gas dynamic virtual nozzle systems as well as high‐viscosity extruders and provides space and flexibility for other liquid injection devices and future upgrades. The liquid jets are confined in a differentially pumped catcher assembly and can be replaced within a couple of minutes through a load‐lock. A two‐microscope imaging system allows visual control of the jets from two perspectives.